2013
DOI: 10.3389/fcimb.2013.00005
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia vaccines: are we moving forward?

Abstract: The genus Burkholderia consists of diverse species which includes both “friends” and “foes.” Some of the “friendly” Burkholderia spp. are extensively used in the biotechnological and agricultural industry for bioremediation and biocontrol. However, several members of the genus including B. pseudomallei, B. mallei, and B. cepacia, are known to cause fatal disease in both humans and animals. B. pseudomallei and B. mallei are the causative agents of melioidosis and glanders, respectively, while B. cepacia infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 122 publications
(136 reference statements)
1
74
1
Order By: Relevance
“…Therefore, the incorporation of antibody-inducing proteins is important when designing a subunit vaccine against Burkholderia. Nevertheless, it is currently understood that balanced cellular and humoral immune responses will be required for vaccine-induced protective immunity against B. pseudomallei and B. mallei (29,(36)(37)(38). Interestingly, in the present study, there does not appear to be a direct correlation between antibody titers (anti-LPS or antiprotein) and protection.…”
Section: Use Of Novel Burkholderia Antigens For Nanovaccinescontrasting
confidence: 61%
“…Therefore, the incorporation of antibody-inducing proteins is important when designing a subunit vaccine against Burkholderia. Nevertheless, it is currently understood that balanced cellular and humoral immune responses will be required for vaccine-induced protective immunity against B. pseudomallei and B. mallei (29,(36)(37)(38). Interestingly, in the present study, there does not appear to be a direct correlation between antibody titers (anti-LPS or antiprotein) and protection.…”
Section: Use Of Novel Burkholderia Antigens For Nanovaccinescontrasting
confidence: 61%
“…There has been significant effort in the past decade to devise vaccines for glanders and melioidosis, but many challenges remain, including considerable gaps in understanding immune mechanisms and correlates of protection, the availability of efficient vaccine delivery platforms, and the identification and characterization of protective antigens (57)(58)(59)(60)(61)(62)(63)(64). Given their important roles in pathogenicity, overall structure, and cellular location at the host-pathogen interface, autotransporter proteins (ATs) represent excellent targets for developing countermeasures (65)(66)(67)(68)(69)(70)(71)(72)(73)(74).…”
mentioning
confidence: 99%
“…Recent work has shown that a vaccine would be a cost-effective intervention in Thailand if used in high-risk populations such as diabetics [10]. However, at present there is no available human vaccine, though a wide range of candidates including live attenuated mutants, killed cells, protein or polysaccharide sub-units and naked DNA vaccines have been tested in mice (for recent reviews see [11][12][13]). All of these vaccines are able to induce some protective immunity, protecting against the acute form of the disease.…”
Section: Introductionmentioning
confidence: 99%